Anatomy of the Sovereign Insolvency of Sri Lanka - Sarvananthan, M. (Social Science Research Network, 2023)
Sri Lanka defaulted on repayment of its external public debt in April-May 2022 for the first-time in its history, and was the first Asian country to do so in the past quarter century. This Working Paper provides an incisive account of the repeated blunders made by successive Governors as well as the Monetary Board of the Central Bank of Sri Lanka (CBSL) since 2006 to date, disregarding the saner counsel by retired senior professional staff of the CBSL, and independent economists and financial analysts. This ‘Insight’ calls for accountability for the actions and inactions of the Central Bank of Sri Lanka since 2006 to date on the premise that authority and power come with responsibility and accountability.
Keywords: Accountability; Central Bank of Sri Lanka; Corruption; IMF; Sovereign Default